Produksi Film PSA â€œKita Indonesiaâ€ Sebagai Media Komunikasi Berbasis Multimedia - Tsabiet, Muhammad; Supriyadi, Supriyadi (Universitas Bina Sarana Informatika, 2018)
Film is one powerful tool in the hands of people who use it effectively for a purpose, especially for the general public as well as children who do use more emotional aspects than their rational aspects, and immediately speak to the hearts of the audience convincingly. Films are also very helpful in the learning process, what is respected by the eyes and heard by the ears, faster and easier to remember than what can only be read or only heard. AKOM BSI Jakarta Program Study Â Broadcasting develops its expertise to try to penetrate the film world through multimedia technology. In collaboration with the Ministry of Home Affairs (Kemendagri) during the